Pengaruh Keikutsertaan OSIS dan Motivasi Belajar Terhadap Hasil Belajar Siswa di MTs Negeri 2 Kota Malang - Izadatul Husna (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
Education result of student becomes measurement for learning achievement which has done by students. Level of student achievement can be considered from how high students can achieve result in the learning. There are many factors will influence and appear learning difficulties for student, if learning needed is not completed. At least, it will obstruct and influence achievement of learning result. If contemplated from external factor of students, there are two factors can influence learning result of student, that are participation of student on intra-school organization student and learning motivation which become variables on the research. General objectives of the research is to understand the influence between student participation on intra-school student organization to learning result of student, the influence of learning motivation to learning result, and also the influence of student participation on intra-school student organization and learning motivation to learning result of student in MTsN 2 Kota Malang. Approach used in the research is quantitative approach and kind of research is explanatory. Explanatory is research with the aim to analyze relation between one variable to another, or how a variable influence another variable. Instrument used in the research is questionnaire which used to review student participant on intra-school student organization and learning motivation that joined by student. Instrument used in the research to know learning result of student is score of middle examination on even semester, in 2016/2017 academic year. Analyze technique used in the research is bifilar linear regression. The result of research shows that: (1) participation of student on intra- school student organization has significant positive impact to learning result of student with value of nilai thitung 2.157 ≥ ttabel 1.98 value of significant 0,033 < 0,05, (2) learning motivation has significant positive relation to learning result of student with value of nilai thitung 2.219 ≥ ttabel 1.98 and value of significant 0,029< 0,05, (3) result of bifilar linear regression shows that there is positive relation from student participation on intra-school student organization to learning result of student, there is learning motivation to learning result, there is influence between student participation on intra-school student organization and learning motivation in MTsN 2 Kota Malang.